Unravelling the fate of foliar-applied nickel in soybean: a comprehensive investigation - de Oliveira, Jessica Bezerra; Lavres, Jose; Kopittke, Peter M.; Chaney, Rufus L.; Harris, Hugh H.; Erskine, Peter D.; Howard, Daryl L.; dos Reis, André Rodrigues [UNESP]; van der Ent, Antony (My University, 2024)
Background and aims: Nickel (Ni) deficiency has been reported to occur in soybean (Glycine max) grown on leached tropical soils in Brazil. We aimed to determine whether an internal or external Ni supply can compensate for low Ni within the seed by assessing whether the amount of Ni in the seed whether the foliar-application of aqueous NiSO4 influenced the uptake of Ni by the leaf, the nutritional status of the plant, urease activity and growth. Methods: We used Ni-depleted seeds (<0.35 μg Ni per g) and Ni-sufficient seeds (11.1 μg Ni g−1) for hydroponic experiments. Seedlings were grown either with or without an external Ni supply (0 or 0.85 μM Ni in nutrient solution) and either with or without an internal Ni supply (with or cotyledons removed). In addition, we used synchrotron-based micro-X-ray fluorescence analysis to examine the distribution of foliar-applied Ni (50 and 100 mg L-1). Key results: Leaf Ni concentration and urease activity were both enhanced by increasing either the internal (cotyledon seed store) or external (solution) Ni supply. In addition, plants derived from Ni-depleted seed that received external Ni supply had 9.2% higher biomass relative to plants derived from Ni-sufficient seeds which received Ni. When foliar-applied, Ni accumulated in the pedicles of the trichomes within 15 minutes of application, and then moved to the vascular bundles before dispersing further into tissues within 3 hours. Conclusions: Trichomes are an important pathway for foliar Ni absorption in soybean, but there are still major knowledge gaps our understanding of the physiological function of trichomes in the uptake of metal ions from foliar micro-nutrient treatments.
Keywords: Foliar nutrition; Leaf ion absorption; Nickel deficiency; Soybean; XFM